Modified Pelvic Floor Repair in Prolapsed Uterus, with Total Prevention of Vault Prolapse - S, Suthanthira devi (JCDR Research and Publications (P) Limited, 2014)
In and around Ammapettai, a rural area with an economically backward community, 515 cases were operated for prolapsed uteri, by doing modified pelvic floor repairs (Dr. Sunthanthradevi’s method), without any incidence of vault prolapse, with patients being followed up for two years after their surgeries.